Optimization method to obtain appropriate spacing parameters for crop cultivation - Ding, Weilong; Fan, Chengcheng; Xu, Lifeng; Xie, Tao; Liu, Yang; Wan, Zangxin; Max, Nelson (International Journal of Agricultural and Biological Engineering, 2020)
Considering the time-consuming and tedious work of the current methods to control plant layout, which is mostly based on expert experience or field trials, we propose an algorithm to optimize and simulate a planting layout based on a virtual plant model and an optimization algorithm. A functional-structural plant model, which combines the structure and physiological function of plants, is used to construct a planting scene. The planting and row spacing are set as the genetic factors and the chromosomes of the genetic algorithm are encoded with a binary method. The photosynthetic yield of the unit planting area is denoted as the fitness value. By using this method, the intercropping of maize and soybean plants and the sole cropping of rice plants are studied. Experimental results show that the proposed method can obtain a high yield planting plan.Keywords: functional-structural plant models, genetic algorithm, spacing optimization, plant spatial distributionDOI: 10.25165/j.ijabe.20201301.4877Citation: Ding W L, Fan C C, Xu L F, Xie T, Liu Y, Wan Z X, et al. Optimization method to obtain appropriate spacing parameters for crop cultivation. Int J Agric & Biol Eng, 2020; 13(1): 146–152.